A modeling study on utilizing SnS2 as the buffer layer of CZT(S, Se) solar cells. (June 2018) - Haghighi, Maryam; Minbashi, Mehran; Taghavinia, Nima; Kim, Dae-Hwan; Mahdavi, Seyed Mohammad; Kordbacheh, Amirhossein Ahmadkhan
Graphical abstract: Highlights: CZT(S, Se) solar cell is modeled with vertically graded absorber composition based on experimental data. The non-toxic and inexpensive SnS2 has been introduced as a new buffer layer and appropriate alternative for CdS. The measured conduction and valence band positions of PLD grown SnS2 layers are 4.26 eV and 6.11 eV. SnS2 compares well with CdS as the buffer layer of CZT(S, Se) solar cells. Abstract: CdS is conventionally used as the n-type buffer layer in chalcopyrite (CIG(S, Se)) and Kesterite (CZT(S, Se)) solar cells. CdS is toxic and there are wide attempts to find substitutes for it. Here, we suggest SnS2 as a possible alternative. SnS2 films were deposited by pulsed laser deposition (PLD), characterized to estimate carrier concentration and electron affinity values, and the obtained values were used to model a CZT(S, Se) solar cell. The experimental values of a benchmark CZT(S, Se) cell with efficiency of 12.3% were employed to obtain the density and energy position of defects in CZT(S, Se) and validating the model. We observed that SnS2 results in almost identical performance as CdS, showing slightly better current density, due to smaller conduction band offset of 0.21 eV compared to 0.28 eV for CdS.